The Impact of Qiraah on the Determination of Fiqh Law According to Al-Alusi - Lukman; Mardan; Kasim, Amrah; Irham, Muhammad (Jurnal Multidisiplin Madani, 2024)
The purpose of this study is to reveal the relationship between Qiraah and Jurisprudence, the method of Determining the Law of Jurisprudence according to Al-Alusi, and the impact of Qiraah on the Verses of Worship on Determining the Law of Jurisprudence according to Al-Alusi. This research is a qualitative research, the type of research is library research. The data collection method used is literature study. The results showed that; 1). The close relationship between fiqh and qiraah has had a significant impact on the understanding and development of Islamic law. The understanding and expertise in qiraah by the fuqaha provided an additional dimension in the interpretation and application of Islamic law. Thus, the close relationship between fiqh and qiraah became one of the hallmarks of the Islamic tradition of thought. 2) In exploring the verses to find istinbat law, imam al-Alusi uses two main methods, namely bayani and qiyasi methods. 3) The differences in qiraah that affect the istinbat law have given birth to different legal status. This has a significant impact on the process and results of determining the law, such as in the case of worship issues